The Effect of Botanical Fungicides on Anthracnose Disease in Chili Fruit (Capsicum annuum L.) - Syamimi, Nur Kholilah; Hendrival, Hendrival; Khaidir, Khaidir; Hafifah, Hafifah; Usnawiyah, Usnawiyah (Yayasan Pertanian Tropika Indonesia (YPTI), 2022)
Research on the application of billygoat weed, lantana, and cogon grass leaves extracts on anthracnose disease in chili plants. This research aims to determine the fungicidal activity of billygoat weed, lantana, and cogon grass leaves extracts on the growth and development of anthracnose disease in chili plants. This research method includes the extraction of billygoat weed, lantana, and cogon grass leaves, Potato Dextrose Agar (PDA) media preparation, Colletotrichum capsici fungal isolates breeding, and in vitro and in vivo testing. The research was conducted in the laboratory with three types of treatments arranged in a completely randomized design (CRD). The results of in vitro testing showed that billygoat weed, lantana, and cogon grass leaves extracts were able to inhibit the growth of Colletotrichum capsici colonies ranging from 0.50-1.24 cm, 80.58-92.15% inhibitory capacity, 0.16x1060.22x106 spore density at 7 days after inoculation and testing. The results of in vivo testing showed that billygoat, lantana, and cogon grass leaves extracts were able to reduce disease severity between 12.50-16.00%, disease incidence ranging from 26.00-30.00%, and chili fruit weight loss of 28.97-32.92%. Billygoat weed, lantana, and cogon grass leaves extracts have the potential as a botanical fungicide in controlling anthracnose disease in chili plants.